2019
DOI: 10.1002/jcla.23037
|View full text |Cite
|
Sign up to set email alerts
|

The pre‐analytical stability of 25‐hydroxyvitamin D: Storage and mixing effects

Abstract: Background There is an increasing demand for serum 25‐OH VitD testing globally, and this has led to the greater use of automated immunoassays. These may be more prone to non‐specific interference, that is thought to be related to pre‐analytical stability of biological samples. We have investigated the changes in serum 25‐OH VitD concentrations that are caused by storage and mixing conditions, and if such changes are statistical, or clinically important. Methods Blood samples were collected into plain tubes fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…As such, there could be variability of plasma levels regarding the storing period. However, studies confirmed that plasma vitamin D levels can be stable after long-term storage at -20°C [17]. Thus, this restriction will not affect our results.…”
Section: Limitations Of the Studymentioning
confidence: 58%
“…As such, there could be variability of plasma levels regarding the storing period. However, studies confirmed that plasma vitamin D levels can be stable after long-term storage at -20°C [17]. Thus, this restriction will not affect our results.…”
Section: Limitations Of the Studymentioning
confidence: 58%
“…Different storage conditions (fresh samples vs. up to 24 h at room temperature, different centrifuging times/temperature, multiple freeze–thaw cycles) did not significantly affect 25(OH)D values [ 7 , 14 , 16 , 17 , 18 , 19 ]. Long-term stability of 25(OH)D at −20 °C and −80 °C is generally acceptable, although a 15% variation after two months [ 20 ] or significant loss after four months at −20 °C was observed [ 14 ].…”
Section: Methodological Determinantsmentioning
confidence: 99%
“…Preanalytical stability of serum 25-hydroxyvitamin D following long-term sample storage at up to −40 °C has been demonstrated previously. 23 , 24 …”
Section: Methodsmentioning
confidence: 99%